Islamic finance – an alternative way of development of the international finance market. (Journal of Economic Research & Business Administration, 2016)
The market of the Islamic financing has been actively developing recently. The basic condition of its organization is the conformity of Islamic financial products with the requirements of the Koran and norms of the Sharia. Sukuk represents one of the most successful examples of the introduction of the Islamic financing not only into the countries with traditionally Islamic economy, but also into the countries with secular economy. Sukuk has considerable prospects of the development owing to a high investment orientation, constant growth of the Islamic population and requirements of the developed economies, including the Kazakh economy, in the attraction of direct foreign investments from Gulf States. The article addresses the issues associated with the use of tools «Islamic Finance» in the territory of the Republic of Kazakhstan. Advantages and disadvantages of Islamic banking, the basic funding model developed by the Islamic banking system. Positive elements in the conduct of Islamic banking business, can improve the work of banks.The offered measures can promote in many respects the integration of this relatively new financial tool into the world financial system.
Keywords: financing; Islamic banking; investment; capital.